The Study of the Process and Nature of Career Identity Formation in Adolescent Girls for Developing an Awareness and Preparedness Model - Beiranvand, Shirin; Khodabakhshi-Koolaee, Anahita; Falsafinejad, Mohammad Reza; Zare Bahram Abadi, Mehdi (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: Adolescence is a critical period; the identity formed during this time impacts all major life decisions, including career decision-making. This study aimed to assess the effectiveness of an awareness and preparedness model for career decision-making among 11th-grade high school girls in Khorramabad.Methods and Materials: This research was conducted using a sequential exploratory mixed-method design. The study population included 11th-grade female students from Behesht Aein School in Khorramabad during the 2021-2022 academic year. In the qualitative phase, 20 adolescents were selected through purposive sampling, and semi-structured interviews were conducted. The data were then analyzed using conventional qualitative content analysis, and a career decision-making awareness model was developed based on the findings. Then, 30 adolescents were selected through simple random sampling and randomly assigned to experimental and control groups of 15 each. Data were collected using the Dielas Career Identity Questionnaire (1981) and the Betz and Taylor Career Decision-Making Questionnaire (1996). The experimental group received twelve 1.5-hour sessions of the career decision-making awareness model. Data were analyzed using multivariate covariance analysis in SPSS version 25.Findings: In the qualitative results, three main categories emerged: "the process of self-concept discovery," "facilitating factors in the development of career self-concept," and "contextual factors in job selection." In the quantitative results, there was a significant difference between the pre-test (3.87) and post-test (4.8) scores of career identity in the experimental group (P=0.001, ƞ2=0.388, f=17.091). There was also a significant difference in career decision-making scores between the pre-test (2.96) and post-test (3.72) in adolescent girls before and after the career decision-making awareness model (P=0.001, ƞ2=0.893, f=25.327).Conclusion: The awareness model intervention, designed considering the context, environment, and teachings relevant to 11th-grade high school girls, led to increased career identity formation and career decision-making readiness. School counselors can utilize this intervention to assist in career identity formation and enhance career decision-making readiness among adolescents.